Prospective evaluation of the long-term effects of clinical voiding reeducation or voiding school for lower urinary tract conditions in children. Issue 1 (February 2016) - Van den Broeck, C.; Roman de Mettelinge, T.; Deschepper, E.; Van Laecke, E.; Renson, C.; Samijn, B.; Hoebeke, P.
Summary: Introduction: Although the short-term effects of urotherapy as a treatment strategy for lower urinary tract (LUT) conditions have been well documented, the long-term effects remain largely unknown. A better insight into the long-term effects of urotherapy could improve the clinical guidelines for children with incontinence. Objective: This study aimed to investigate the long-term effects (i.e., from 6 months to 2 years) from a clinical voiding reeducation program among children with LUT conditions. Study design: This study was a prospective continuation of the follow-up study of Hoebeke et al. (2011). Thirty-eight children (mean age 9 years) with LUT conditions completed an extensive clinical voiding reeducation program (VS). Data on medication, voiding, drinking, pelvic floor tone, uroflowmetry, and incontinence were recorded 2 years after the VS. These data were compared with the outcomes at 6 months follow-up and at intake before voiding school. Results: Six months after voiding school, 22 children continued having daytime incontinence (ID) and/or enuresis (EN). Six of them became dry at 2 years. Conversely, 16 children were dry at 6 months, of which eight relapsed at 2 years. Whereas all parameters significantly improved 6 months after VS, further improvements from 6 months to 2 years could only be noticed for the proportion of children suffering from overactive bladder (92% at intake, 55% at 6-month follow-up and 18% at 2-year follow-up) (Figure). Fluid intake and pelvic floor tone improved after 6 months, but showed a significant relapse after 2 years ( P  = 0.013, P  = 0.031, respectively). Discussion: Hoebeke et al. (2011) concluded that results continued to improve after VS. No further improvements could be noticed 2 years after VS, although individual shifts were present. The results of the present study underline the value of long-term follow-up to detect those needing ongoing treatment to prevent relapse. Fluid intake and pelvic floor tone deteriorated from 6 months to 2 years. It could be hypothesized that inadequate fluid intake, possibly leading to decreased voided volumes, may be seen as an indicator for upcoming incontinence relapse. It could be stated that adequate fluid intake and pelvic floor tone may play a role in remaining continent for the long term. Study limitations should be considered. The study population was heterogeneous and rather small. Together with other missing values, this could have influenced the results. Conclusion: Close individual, long-term follow-up after clinical voiding reeducation in children is recommended in order to timely detect and prevent potential relapse.